2020
DOI: 10.1155/2020/8164365
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering PD-L1 and CD8+ TILS Expression and Clinical Implication in Cervical Squamous Cell Carcinoma

Abstract: Objective. To investigate the association between programmed death-ligand 1 (PD-L1) coupled with CD8+ tumor-infiltrating lymphocytes (TILS) and the clinicopathological features, along with prognosis of cervical squamous cell carcinoma (CSCC). Methods. 95 patients of CSCC received tumor resection at the Department of Pathology of the First Affiliated Hospital of University of Science and Technology of China (USTC) from 2015 to 2020. Full-automatic immunohistochemistry was applied to measure PD-L1 expression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Patients with a high density of CD8+ TILs in tumors showed a better prognosis than those with a low density of cells. The best prognosis for cervical squamous cell carcinoma patients was shown in the high-density PD-L1−/CD8+ TIL group, and the worst prognosis was shown in the low-density PD-L1+/CD8+ TIL group (42). Burrack reported that the PD-L1 expression was associated with the CD8+ TIL density in pancreatic cancer tissue, implying the tumor immune response and immunogenicity of tumors (43).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a high density of CD8+ TILs in tumors showed a better prognosis than those with a low density of cells. The best prognosis for cervical squamous cell carcinoma patients was shown in the high-density PD-L1−/CD8+ TIL group, and the worst prognosis was shown in the low-density PD-L1+/CD8+ TIL group (42). Burrack reported that the PD-L1 expression was associated with the CD8+ TIL density in pancreatic cancer tissue, implying the tumor immune response and immunogenicity of tumors (43).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we also verified the similar results in HCS-2 cells. Many studies in human clinical SCC tissues have revealed that PD-L1, ezrin, and moesin are widely expressed in laryngeal [41][42][43] and oral [44][45][46][47][48][49] SCCs, PD-L1; and that ezrin are expressed in tongue [50][51][52] and esophageal [53][54][55][56][57] SCCs; and that PD-L1 and moesin are expressed in uterine cervix SCC [58][59][60]. In contrast, radixin expression has been reported only in the human tongue SCC cell line Tca8113 [61].…”
Section: Discussionmentioning
confidence: 99%
“…This is likely, because radixin is a dominant ERM protein in the hepatic tissues and hepatocytes [71]. Given that in contrast to ezrin and radixin, moesin is highly expressed in the human uterine cervix SCC [58][59][60], moesin may regulate the plasma membrane localization of PD-L1 as a predominant ERM protein in BOKU cells and HCS-2 cells, as is the case with ezrin in HeLa and LS180 cells [31,32]. The detailed mechanism by which PD-L1 selects a particular ERM protein as a partner for its plasma membrane localization in several cancer cell types will have to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could actually be due to the fact that these type of carcinomas have high density of CD8+ tumour infiltrating lymphocytes (TILs) [ 17 , 18 ]. The presence of prominent TILs in PD-L1 positive cervical carcinomas is associated with longer survival compared to cervical carcinoma patients with low or no TILs [ 19 , 20 ]. Thus, care is needed when interpreting PD-L1 positivity in relation to prognosis, this has led to development and proposition of the immune-score in predicting clinical outcomes in cervical carcinoma [ 21 ].…”
Section: Introductionmentioning
confidence: 99%